Intelligent electric quantity managing and monitoring system for power battery - DING SHENPING (2018)
The invention discloses an intelligent electric quantity managing and monitoring system for a power battery. The intelligent electric quantity managing and monitoring system comprises a main control unit, a displaying module, a storage module, a detecting module, a shunting unit, an analog quantity collecting unit and a battery; the main control unit is in control connection with the displaying module, the storage module and the detecting module, the shunting unit is electrically connected with the detecting module and the battery, and the storage module is electrically connected with the maincontrol unit and the battery; and the intelligent electric quantity managing and monitoring system for the power battery further comprises the analog quantity collecting unit, and the analog quantitycollecting unit is in control connection with the main control unit and the storage module. In this way, the intelligent electric quantity managing and monitoring system for the power battery is highin reliability and low in